On an approximate method for calculating filters based on acoustic surface waves - CEROWSKI, Zenon; OPILSKI, Aleksander; PUSTELNY, Tadeusz; URBAŃCZYK, Marian (Archives of Acoustics, 1976)
The work describes an electric filter consisting of interdigital transducers deposited on piezoelectric substrate. A method has been presented for computing the transducer parameters with an assumed amplitude-frequency cha¬racteristic. The filters produced on the basis of calculated transducer parameters were tested and the results are given in this paper.